Typology of Carrots, Sticks, and Sermons: Tracing Its Influence on the Discipline of Public Policy - Karol Olejniczak; Tomasc Kupiec; Dominika Wojtowicz (Journal of MultiDisciplinary Evaluation)
Background: The 1998 book "Carrots, Sticks & Sermons: Policy Instruments and Their Evaluation" introduced a seminal typology categorizing policy tools by their mechanisms of influence. Despite its potential to shape policy theory and practice, its broader disciplinary impact and citation patterns remain underexplored. This article evaluates the book's legacy in public policy literature while testing bibliometric methods, including emerging generative artificial intelligence (GAI) tools for research synthesis.